DIFRAKSI GELOMBANG PADA SILINDER 8ESAR DENGAN MILD SLOPE EQUATION - Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
ABSTRACTThis research is aimed to know the process of wave diffractionaround the large cylinder of offshore structure using finite elementmethod. This model chosen because of some reasons, i.e thecomplication of offshore structure's shape which are caused difficultiesto conduct physical model solving. The other excess of this numericalmodel is cheaper and easier than physical model conducted in thelaboratorium.The equation of wave diffraction can be formulated as Helmholtzequation. A second approach can be developed by Mild Slope Equation,which is assumed that the depth is constant. The Helmholtz equationwas done using finite element method with linear triangle interpolation.With finite element method, the complicated domain area can be solvedmore easily and effectively.The result shows that the use of finite element method is stilladequate to solve Helmholtz equation' for period 8, 9 and 10 second.For period of 8 second numerical error produce the wave heightdifference of 0,36 m. The numerical model is then easily edited toanalyze another offshore structures.Keywords: diffraction, cyllinder, finite element